"Gone with the land": Effects of land expropriation on health and subjective well-being in rural China. (January 2022) - Zhao, Xiaohang; Jin, Lei; Sun, Skylar Biyang
Abstract: Objective: Few studies have investigated the relationship between land expropriation and health and subjective well-being (SWB) in China. This study examines the impacts of land expropriation on health and SWB among Chinese farmers aged 16–85 years and explores whether these impacts vary with socioeconomic conditions. Methods: We utilized longitudinal data from the China Family Panel Studies, a nationally representative survey. The analytic samples included over 10, 000 individuals and over 30, 000 person-year observations. Individual fixed-effects models were employed to eliminate the omitted-variable bias derived from time-constant unobserved confounders. Results: Land expropriation was harmful to health and SWB. First-time land expropriation increased the risks of physical discomfort, chronic diseases, hospitalization, and perceived health decline; raised the frequency of feeling depressed; and decreased self-rated health, life satisfaction, subjective social status, and confidence about the future. Repeated land expropriation and past land expropriation increased the risks of chronic diseases, raised depressive symptom severity, and lowered self-rated health and life satisfaction. Repeated land expropriation also elevated the risk of perceived health decline. In addition, preexisting household income per capita and baseline county-level GDP per capita buffered the adverse impacts of first-time land expropriation. Conclusion: This study reveals the adverse impacts of land expropriation on health and SWB and highlights the importance of providing support to land-taken farmers to alleviate such detrimental effects. Highlights: Prior research on the health and well-being consequences of land expropriation in China yielded mixed findings. Individual fixed-effects models are employed to draw causal relationships. Land expropriation harms Chinese farmers' health and subjective well-being. The detrimental effects of land expropriation are more profound among more disadvantaged farmers.